The performing pianist's guide to fingering - Banowetz, Joseph 1934-2022 (Indiana University Press, 2021)
The Performing Pianist's Guide to Fingering will be useful to the advanced pianist and to instructors looking to guide students in improving this important art
Description based on publisher supplied metadata and other sources
Keywords: Klaviertechnik